2009
DOI: 10.1080/07420520902821176
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and Metabolic Syndrome: Respective Impacts of Job Strain, Physical Activity, and Dietary Rhythms

Abstract: The impact of shift work on cardiovascular disease (CVD) risk factors and metabolic syndrome are not yet completely understood. The objectives of this study were to evaluate the impact of shift work on metabolic syndrome according to two different definitions in a population of strictly rotating shift workers (3x8 h) compared to paired counterparts working only day hours, and to study whether shift work itself is a determinant of metabolic syndrome after taking into account a large panel of confusing factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
240
6
25

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(288 citation statements)
references
References 53 publications
17
240
6
25
Order By: Relevance
“…Interestingly however, previous studies consistently report little or no difference between the dietary intake of shiftworkers and non-shiftworkers [1,9,25,26] although the frequency and timing of meals is very potently disturbed, [26] and the risk of shiftworkers having metabolic syndrome was associated with the timing of meals but not with overall energy intake. [25] Human circadian rhythms in glucose and insulin sensitivity are optimised towards ingestion of food in daytime, yet shiftwork often necessitates that food is ingested at night when these endogenous metabolic rhythms are not prepared for food. Experimental studies in humans and animals have shown that this metabolic mismatch can disrupt blood glucose and triglyceride rhythmicity, [27] dampen liver transcriptional rhythms, [28] and ultimately lead to compromised pancreatic beta cell function, decreased energy expenditure, leptin resistance, and diabetes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly however, previous studies consistently report little or no difference between the dietary intake of shiftworkers and non-shiftworkers [1,9,25,26] although the frequency and timing of meals is very potently disturbed, [26] and the risk of shiftworkers having metabolic syndrome was associated with the timing of meals but not with overall energy intake. [25] Human circadian rhythms in glucose and insulin sensitivity are optimised towards ingestion of food in daytime, yet shiftwork often necessitates that food is ingested at night when these endogenous metabolic rhythms are not prepared for food. Experimental studies in humans and animals have shown that this metabolic mismatch can disrupt blood glucose and triglyceride rhythmicity, [27] dampen liver transcriptional rhythms, [28] and ultimately lead to compromised pancreatic beta cell function, decreased energy expenditure, leptin resistance, and diabetes.…”
Section: Discussionmentioning
confidence: 86%
“…Shiftworkers were more likely to have higher BMI despite higher physical activity, yet there is little evidence that they eat more than non-shiftworkers. [4,25] It may be more beneficial to modulate the timing and frequency of their meals and activity rather than volume. However, even if this were possible, it will not address the fundamental uncoupling of physiological and environmental timing that most likely underlies the effects of shiftwork on metabolism and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation results in a single amino acid change in CK1ε binding domain of the hPER2 molecule, which affects the level of its phosphorylation and stability [55]. More recently, a number of epidemiological studies have suggested that people who work in rotating shifts or at night show a higher incidence of carcinogenesis, heart disease, and metabolic syndrome caused by circadian desynchronization [56][57][58]. These people also have higher rates of errors and accidents and often experience a significant loss of alertness and ability to make decisions.…”
Section: Circadian-related Disordersmentioning
confidence: 99%
“…Or, nous montrons que CLOCK, seul ou avec BMAL1, est capable d'activer la transcription de Lpl [6]. Cette dérégulation de la Lpl, qui favoriserait l'utilisation des acides gras dans le muscle et l'adipogenèse dans le tissu adipeux blanc, aurait pour origine la surexpression de CLOCK en l'absence de REVERB (Figure 1 [1,2]. Le simple fait de nourrir des souris avec la même quantité de nourriture pendant la phase de repos au lieu de les nourrir pendant la phase active conduit à une augmentation de prise de poids [3].…”
Section: Les Auteurs Déclarent N'avoir Aucun Lien D'intérêt Concernanunclassified